W ACANA SAINS DALAM NOVEL SUPERNOVA EPISODE KSATRIA, PUTERI, DAN BINTANG JATUH - Chasanah, Ida Nurul (ATAVISME, 2008)
This paper is aimed to describe the stories of Supernova 1 to identify the fiction and non? fiction dialectics and also to represent science aspect in Supernova novel Episode Ksatria, Puteri, dan Bintang Jatuh (Supernova 1) through the relationship of intertextuality. We can find five stories in novel Supernova 1, they are the stories about Ruben-Dhimas, Ferre-Rana-Arwin, Diva, Supernova, and classic fairy tale knight, princess, and falling star. The dialectics between fiction and non-fiction in Supernova I are found through some indications, such as cover, tittle, scientific process of writing method in fiction such as the use of footnote, the insert of bibliography and index, and also preface, the dynamic of character, events arragernent that make plot, mentioning 'keping' to change chapter. Science aspect in Supernova 1 are not only a pacth but they are represented in text structure. The transformation of science elements in novel Supernova 1 are more affirmative with hypogram that is referred by some expansion. That science elements are astronomy, chaos theory (it covers Lorenz butterflies and fractal geometri), Schrodinger, co-evolution, and non-linear theories.